Preserving Qur’an through blind eyes: self-regulation of blind people in memorizing the Qur’an - Taufik, Taufik; Kurniawan, Riza; Ibrahim, Rahimah; Abdullah, Haslinda; Widhiastuti, Hardani (Routledge, 2024)
The present study aimed to investigate the self-regulation of blind people in memorizing the Qur’an. Eight blind Qur’an memorizers were interviewed about the internal motivation of Qur’an memorization, self-regulation, and Qur’an memorization with vision impairment. The research was conducted using a phenomenological approach on exploration of the lived experience of eight blind memorizers, who were selected using purposive and snowball techniques. Data were transcribed verbatim and analyzed by Moustakas’ phenomenological method. The findings revealed that (1) gratitude was the main factor in regulating the rest of the metacognitive process among the blind memorizers, (2) the motivation to benefit for others served as a metacognitive purpose for the blind memorizers, (3) memorization strategies including the repetitive listening at a specific time and place were used in improving and maintaining the memorization, and (4) the belief in not to see and commit sins through eyes enabled the blind memorizers to maintain the purity of heart and made it easier for them to memorize the Qur’an. Informants described two spiritual meanings of the self-regulation within themes of gratitude and maintenance of heart purity associated with the Qur’an memorization. Gratitude is associated with the self-efficacy in the motivational dimension, whereas the reflective aspect of heart purity due to being blind is related to the metacognitive component of self-regulation. The findings provided new knowledge and understanding of blind individuals’ experiences in the self-regulation and memorization of the Qur’an.